2010
DOI: 10.1353/sof.2010.0002
|View full text |Cite
|
Sign up to set email alerts
|

Military Spending and Economic Well-Being in the American States: The Post-Vietnam War Era

Abstract: Using growth curve modeling techniques, this research investigates whether military spending improved or worsened the economic well-being of citizens within the American states during the post-Vietnam War period. We empirically test the military Keynesianism claim that military spending improves the economic conditions of citizens through its use by politicians as a countercyclical tool to reduce the negative effects of economic downturns. However, due to deindustrialization and the emergence of the "new milit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
11
2
2
Order By: Relevance
“…Second, the localized effects hypothesis suggests that the consumption‐based effects of defense personnel spending on military bases and civilian personnel of the Defense Department will have more immediate effects on urban economies than the agglomeration‐based effects of defense procurement contracts that are more geographically diffuse. This represents an important departure from previous studies that show that defense procurement spending has larger effects at the state level (Borch and Wallace, 2010) and cautions against the assumption that outcomes of military spending at the federal or state levels extend automatically to urban areas. Third, the gunbelt hypothesis predicts that federal defense spending has affected urban economies unevenly, benefiting metropolitan areas in some regions of the country more than others 5 .…”
Section: Insights From Urban Political Economy Theorycontrasting
confidence: 69%
See 3 more Smart Citations
“…Second, the localized effects hypothesis suggests that the consumption‐based effects of defense personnel spending on military bases and civilian personnel of the Defense Department will have more immediate effects on urban economies than the agglomeration‐based effects of defense procurement contracts that are more geographically diffuse. This represents an important departure from previous studies that show that defense procurement spending has larger effects at the state level (Borch and Wallace, 2010) and cautions against the assumption that outcomes of military spending at the federal or state levels extend automatically to urban areas. Third, the gunbelt hypothesis predicts that federal defense spending has affected urban economies unevenly, benefiting metropolitan areas in some regions of the country more than others 5 .…”
Section: Insights From Urban Political Economy Theorycontrasting
confidence: 69%
“…It is less suited to explain regional and localized concentrations in defense spending that have become more prominent in the second period. Although some recent research on this period has demonstrated that both the causes (Wallace, Borch, and Gauchat, 2008) and consequences (Borch and Wallace, 2010) of military spending at the state level are consistent with a military Keynesian interpretation, there has been no research to date at the metropolitan level. Without modifications, the military Keynesian perspective has limited capacity to explain the concentration of military spending in certain metropolitan areas, its contribution in the uneven economic development of different regions in the country, and its differential consequences for metropolitan labor markets and economic conditions.…”
Section: The Military Keynesian Perspectivementioning
confidence: 98%
See 2 more Smart Citations
“…In 2013 alone, growth in GDP would fall by 25%." The local economic impact of defense spending has been studied by sociologists Casey Borch and Michael Wallace (2010), who showed that states with high military spending do better economically. In 2012, as defense spending shrank in the U.S. by 3%, this had a negative impact on the growth of the whole economy: one estimate put that impact as causing half a percentage point slowdown in growth (USA Today 2012).…”
Section: Resultsmentioning
confidence: 99%